Regulaç\~ao e emprego: O caso da Convenç\~ao no 158 da Organizaç\~ao Internacional do Trabalho - Adolfo Sachsida; Mário Jorge Cardoso de Mendonça; Antonio Negromonte Nascimento Junior (Instituto de Pesquisa Econômica Aplicada (IPEA), 2016)
– Although it is a little known fact the Convention no 158 of International Labor Organization (ILO) which prohibits the dismissal of an employee without cause ruled in Brazil from 10 April to 20 November 1996 and thereby providing an excellent opportunity to evaluate the effect of regulation on job market. Using panel data from montly survey of employment we applied a Probit model to check the effects of the introduction of this rule on Brazilian labor market. Our results demonstrate that during the period of validity of the Convention no 158 both the probability of an individual getting a job as the probability of entering the formal labor market suffered negative effect.
Keywords: J08; J88; C25; 330; regulation; Convention no 158; panel data; probit model